KEPEMIMPINAN ISLAM DAN KONVENSIONAL (Sebagai Studi Perbandingan) - Siti Aminah Chaniago (IAIN Pekalongan, 2010)
The majority population of Indonesia is Moslem. The leadership of Islamic system is dominant to run the organization, although the regulation of the country does not adopt Islamic system. Now, How to compare the leadership of Islam to conventional and how to implement both of the regulation? Because the leadership influences the product and goal of organization either the family or public organization or company or country leadership, etc. The other hand, the success of organization depends on the leadership. This article tries to give the comparison between Islamic leadership and conventional and how to get the synergy both of them.